Coexistence of blaNDM–5 and tet(X4) in international high-risk Escherichia coli clone ST648 of human origin in China - Shafiq, Muhammad; Zeng, Mi; Permana, Budi; Bilal, Hazrat; Huang, Jinhu; Yao, Fen; Algammal, Abdelazeem Mohamed; Li, Xin; Yuan, Yumeng; Jiao, Xiaoyang (Frontiers in Microbiology, 2022)
The emergence of pathogens is conferring resistance to last-resort therapies such as tigecycline, colistin, and carbapenems, limiting the therapeutic options, and raising concerns about the emergence of new “superbugs.” This study reports the first incident of a blaNDM–5 and tet(X4) co-harboring Escherichia coli with resistance to carbapenem and tigecycline recovered as the causative agent of a urinary tract infection in a 94-year-old patient. The E. coli strain ECCL209 carries multiple resistance genes [i.e., blaTEM–1B, blaNDM–5, blaCMY–2, aadA22, florR, erm(B), mph(A), erm(42), lnuG, qnrS1, and sul2] and exhibits resistance to almost all clinically used antibiotics. MLST analysis found that the strain belongs to ST648, considered a worldwide high-risk pandemic clone. Moreover, multiple plasmid incompatibility types were detected, i.e., IncHI1A, IncHI1B, IncFII, IncFIA, IncFIB, IncQ1, Col, and IncX4. Genetic analysis revealed that blaNDM–5 and tet(X4) genes were localized on two hybrid plasmids with multiple replicons. Continuous monitoring studies are suggested to quantify the antimicrobial resistance and assess the dissemination of such superbugs into a human healthcare setting.